Pedagogical Basis Of Ethical Culture For Primary Class Students And Its Analysis - Shohnoza Zaripboyevna Matupayeva (Euro Asian Journal Publishing, 2024)
the article discusses approaches to the formation of the moral culture of elementary school students. The "Uzbekistan-2030" strategy sets the tasks of qualitative development of primary education until 2026 and material and moral support of primary school students. In this regard, the formation of the moral culture of elementary school students is also considered an important indicator of the quality of education. Here, we draw your attention to the analysis of approaches to the formation of the moral culture of elementary school students
Keywords: learner; education; primary school